Application of Infrared with Different Waves and Its Effect on Organoleptic of Dairy Milk - Rosidi Azis; Muhammad Helmi Hakim (Chalaza Journal of Animal Husbandry, 2021)
Infrared applications have been widely used to reduce microorganisms in a product and food preservation. Milk is a food product that quickly decomposes, where the changes can be observed organoleptically. This study aimed to test infrared with various wavelengths of milk and observe changes in the organoleptic of milk. The method used was that the dairy milk samples were treated with infrared (IR) exposure of 880 nm and 940 nm. Observation of the changes in milk organoleptic, namely color, taste, and smell. The effectiveness of IR 880 nm has a better ability than IR 940 nm for smell and taste, while for IR 940 nm, color is better than IR 880 nm at 1 - 4 hours, and at 5 hours with 940 nm IR it changes white-brownish.